Installation and maintenance for air conditioning / Mohamad Hariz Suffiyan Mohd Raffi - Mohd Raffi, Mohmad Hariz Suffiyan (Universiti Teknologi MARA, Perak, 2022)
To accomplish this diploma course, we must complete 20 weeks of industrial training, which is contained in our course outline and must be completed during our diploma's fifth semester. This industrial training began on August 23, 2021 and will end on January 7, 2022. During the industrial training, the selected supervisor will monitor and supervise us. My industrial training in A&A MEGAH SDN. BHD., which is based in Kuantan, Pahang. It is a construction company that provides building maintenance, repair, and other services. The owner of this company, Encik Mohd Azlan Bin Mohd Jubli, founded it on the 20th of June 2020. This business specializes in air conditioning installation, electrical work, and other building services like housekeeping, painting, and laundry. The project that will be working on involves installing and maintaining air conditioners in all of Telekom Malaysia Berhad's buildings. My managing director, who is also the company's owner, help me in handling all aspects of the business, including office work and tender/quotation preparation, as well as completing all outstanding tasks, such as vendor and supplier registration. Because this was the fifth company from the founder, my team assisted me in completing this work.The conclusion is that air conditioning maintenance should be performed to avoid any failures or system failures. I'm hoping that this report will come in handy as a reference in the future.